Examine the significance of the facial makeup pattern used in the Sichuan Opera and its interpretation - Yating, Wu; Abdul Rahman, Ahmad Rizal; Perumal K. M. W., Velu; Siow, May Ling (American Linguist Association, 2022)
Sichuan Opera is a traditional Chinese opera in Chongqing. It is the most well-known local opera in Sichuan and a cultural symbol. This is a cultural symbol passed down through generations of performers. This makeup reflects the personality traits and aesthetic sensibilities of the Sichuan people, as well as the traditional Chinese opera facial makeup art. As a result, Sichuan Opera distinguishes itself from other operas and has become a global symbol of China's strength and resilience. Sichuan Opera facial makeup has a distinct artistic shape, vibrant colours, and intricate decorative patterns. Through their facial makeup, the characters' invisible, abstract and complex inner worlds, thoughts and emotions are displayed incisively and vividly. The pattern design of Sichuan Opera facial makeup reflects the artist's perception of life and opera characters, and it has both artistic and practical value. This paper aims to uncover the artistic value of the Sichuan Opera facial mask's graphic expression through a detailed analysis of the facial makeup structure, lines, and colours. It is no longer limited to opera, but is now widely used as a modelling tool in modern design.